Psychedelic drug use and schizotypy in young adults - Lebedev, Alexander V. (Sci Rep, 2021)
Despite recently resurrected scientific interest in classical psychedelics, few studies have focused on potential harms associated with abuse of these substances. In particular, the link between psychedelic use and psychotic symptoms has been debated while no conclusive evidence has been presented. Here, we studied an adult population (n = 1032) with a special focus on young (18–35 years) and healthy individuals (n = 701) to evaluate the association of psychedelic drug use with schizotypy and evidence integration impairment typically observed in psychosis-spectrum disorders. Experimental behavioural testing was performed in a subsample of the subjects (n = 39). We observed higher schizotypy scores in psychedelic users in the total sample. However, the effect size was notably small and only marginally significant when considering young and healthy subjects (Cohen’s d = 0.13). Controlling for concomitant drug use, none of our analyses found significant associations between psychedelic use and schizotypal traits. Results from experimental testing showed that total exposure to psychedelics (frequency and temporal proximity of use) was associated with better evidence integration (Cohen’s d = 0.13) and a higher sensitivity of fear responses (Cohen’s d = 1.05) to the effects instructed knowledge in a reversal aversive learning task modelled computationally with skin conductance response and pupillometry. This effect was present even when controlling for demographics and concomitant drug use. On a group level, however, only difference in sensitivity of fear responses to instructed knowledge reached statistical significance. Taken together, our findings suggest that psychedelic drug use is only weakly associated with psychosis-like symptoms, which, in turn, is to a large extent explained by psychiatric comorbidities and use of other psychoactive substances. Our results also suggest that psychedelics may have an effect on flexibility of evidence integration and aversive learning processes, that may be linked to recently suggested therapeutic effects of psychedelic drugs in non-psychotic psychiatric populations.